RESIDUAL STRESS ANALYSIS IN SEAMLESS API X60 STEEL GAS PIPELINES (Sciences & Technologie. B, Sciences de l'ingénieur, 2004)
This study is concerned with the analysis of residual strain and stress distributions through the wall of an API X60 grade high strength steel gas pipe. Residual stresses were measured using the BRSL method. This technique is based on the relaxation of stresses by splitting the tube in the longitudinal direction. Displacement measurements while notching indicated important shape changes before final split. Meanwhile, strain gages are used to monitor in real time strain behavior as a function of notch depth. It is found that relieved strains (µm/m) evolved from positive towards negative values in bored out and turned down cases. Circumferential residual stress distribution is obtained using both Mesnager-Sachs and Crampton equations. It is concluded that the latter gave realistic values as the distribution depicted compressive stresses on the outer layers and tensile stresses towards the pipe bore